The in vitro inhibition of adrenal steroidogenic enzymes and modulation of adrenal hormone production by Sceletium tortuosum - Johannes, Inge (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.